Screening of Personality Types of Adolescents in Senior High Schools in Tangerang City: Skrining Jenis Kepribadian Remaja di SMA Negeri Kota Tangerang - Wijoyo, Eriyono Budi; Qolina, Elly; Suryati, Tati; Indriani, Indriani; Mashito, Dewi (Jurnal Pengabdian Masyarakat Kesehatan Terkini, 2025)
Adolescence is a phase in which adolescents enter an unstable age regarding behavior and attitude. This is due to the adolescent's personality type, which will influence how they behave. One of the adolescent ages is someone who enters high school (SMA). The method used in this community service involved 77 adolescents who attended senior high schools in Tangerang City. Furthermore, the community service conducted online screening of adolescent personality types using e-forms. The results obtained from 77 adolescents were that 38 adolescents (49.3%) had extrovert personality types, 27 adolescents had introvert personality types, and the remaining 12 adolescents (15.6%) had ambivert personality types. The activities carried out in this community service included conducting personality screening, counseling on adolescent age and psychological problems in adolescents, and FGD (Forum Group Discussion). It was found that adolescents with personality types need assistance from health workers or teachers to express good attitudes. Furthermore, there needs to be collaboration between schools, health centers, and health services to carry out further activities, especially to strengthen adolescents' mental health.